Application of a natural aminopolysaccharide in seed film-coating for pest control and cotton growth - Zeng, DeFang; Mei, Xiang (Plant Breeding and Seed Science, 2012)
Cotton suffers attacks of various pests that result in a decreased yield. Until recently, the chemical control of pests was achieved through seed film-coating treatment with toxic insecticides. The natural aminopolysaccharide extracts from crab is a promising candidate as a repellent to protect cotton from Aphis gossypii Glover and Helicoverpa armigera Hubner. Experiments were conducted to study the effect of aminopolysaccharide on pest control, seed germination, plant growth and lint yield. Results indicated that all aminopolysaccharide treatments of different content repelled pests efficiently and increased significantly seed germination, plant growth and cotton yield. The natural aminopolysaccharide extracts from shrimp is a promising candidate as a repellent to protect cotton from Aphis gossypii Glover and Helicoverpa armigera Hubner. The application of the potential aminopolysaccharide by seed coating is an appropriate option for controlling pests and avoiding environmental pollution.